Double Addition of Organometallics to Nitriles: Toward an Access to Tertiary Carbinamines. Issue 2 (9th November 2016) - Pearson‐Long, Morwenna S. M.; Boeda, Fabien; Bertus, Philippe
Abstract: As depicted in many textbooks, the addition of organometallics to nitriles is generally limited to a single addition, providing ketones after acidic hydrolysis. However, the double addition, leading to tertiary carbinamines is also possible, as demonstrated as early as 1939 by the double addition of allyl Grignard reagents to α‐ethoxyacetonitrile. Since this seminal result, and stimulated by the biological importance of the so‐obtained carbinamines, efforts were devoted to expand the scope of the double addition of organometallics to nitriles. This review presents these different approaches which have led to short accesses to tertiary carbinamine derivatives. Particularly interesting is the double addition of different organometallics, which opens the way towards the straightforward asymmetric synthesis of tertiary carbinamines from nitriles. Abstract :